Influence of PET fiber geometry on the mechanical properties of concrete: an experimental investigation. Issue 7 (8th August 2016) - Marthong, Comingstarful; Sarma, Deba Kumar
Abstract : Polyethylene terephthalate (PET) fibers are generally used as a discrete reinforcement in the substitution of steel fiber for enhancing the tensile strength as well as improving the ductile property of concrete. PET fibers can be produced by hand cutting from PET bottles or through mechanical slitting. Straight slit sheet fibers obtained from the former process normally result in a weak bond with the concrete matrix and they can slip out at low loads. To improve the anchorage effect, three additional PET fibers with varying geometry (flattened end slit sheet, deformed slit sheet and crimped end sheet) were considered in the present study. The influence of fiber geometry on the mechanical properties of cylindrical and prismatic concrete specimens was investigated. The test results show that the fibers' geometry has a marginal effect on the workability of concrete but a significant contribution to the mechanical properties of concrete.